2011
DOI: 10.1179/1743284711y.0000000074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spiral geometries on grain selection during casting of single crystal superalloys

Abstract: Grain texture evolution in starter block during single crystal (SX) casting with a grain selector had been investigated. Several spiral grain selectors with different spiral geometries were designed to investigate the effects of spiral geometries on grain selection in spiral passage. The results indicated that the percentage of grains with a deviation angle of <10° from the axial orientation increased simultaneously with distance from the chill plate. When the distance reached 36·1 mm, nearly 90 of the grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The modified Bridgman directional solidification furnace was employed. During the preparation of single crystals with the grain selector, geometric parameters of the spiral grain selector were based on the findings of Gao et al [11] . When single crystals were prepared with the seeding technique, in order to obtain seed crystals which can meet the requirements, the orientation of the seed crystal was measured and cut, as shown in Fig.1, where θ represents the orientation of the deviation angle of the single crystal and θ seed represents the orientation of the deviation angle of the seed crystals which were cut from the single crystal.…”
Section: Methodsmentioning
confidence: 99%
“…The modified Bridgman directional solidification furnace was employed. During the preparation of single crystals with the grain selector, geometric parameters of the spiral grain selector were based on the findings of Gao et al [11] . When single crystals were prepared with the seeding technique, in order to obtain seed crystals which can meet the requirements, the orientation of the seed crystal was measured and cut, as shown in Fig.1, where θ represents the orientation of the deviation angle of the single crystal and θ seed represents the orientation of the deviation angle of the seed crystals which were cut from the single crystal.…”
Section: Methodsmentioning
confidence: 99%
“…A grain selector generally consists of a starter block, a selector part and a connector part. Prior studies [7,8,9,10,11,12,13] suggest that the geometries of the starter block and the selector part of grain selectors in particular can affect significantly grain selecting efficiency and the crystallographic orientation of the selected grain. Dai et al [8,11,13] have studied the microstructure evolution and grain competitive growth in spiral grain selector and suggested that the spiral selector becomes more efficient in grain selection with a smaller spiral thickness (dT), a larger spiral diameter (dS) and smaller takeoff angle.…”
Section: Introductionmentioning
confidence: 99%
“…A granulator usually consists of three parts: the starter block, the connecting part, and the granulator part. Some studies [6,7,8,9] have shown that the geometric shape of the grain selector has an important influence on the selection efficiency of grains and the orientation of grains. Among them, a continuous helical structure of helical selectors is the most widely used because of its high efficiency [10].…”
Section: Introductionmentioning
confidence: 99%